L’Île-aux-Coudres : Population et économie - Martin, Yves (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1957)
During the summer of 1954, a study of Ile-aux-Coudres was undertaken by the writer on behalf of the Planning Service of the Province of Québec. The results of this survey are based primarily on the demographic and economic factors relevant to the island.The 1728-1790 period is considered as a period of settlement at the end of which there are 500 inhabitants. The second period (1790-1870) is marked by two facts, a demographical stability, with a total increase of population from 566 to 710, and an economic stagnation due principally to the lack of resources. The dominant economic activity is agriculture, with some fishing and « navigation » as part-time occupations. Several islanders are sailors and navigators on the schooners and steamers that sail on the Saint-Lawrence. From 1870 until 1954, the population bas more than doubled and the main economic activities in 1954 are illustrated in table V, with agriculture in first place followed by the group of « seasonal employees » that leave the island in the summer to work as stevedores in Montréal. After 1930, the Ile-aux-Coudres is not isolated as it used to be, due to a new ferry-boat plying between the island and the mainland and the improvement of the main highway from Québec to Baie-Saint-Paul.The problem of the island is the lack of equilibrium between its resources and its population. Too many residents gain their living outside the island, and agriculture as a basic activity, even if improved, is unable to sustain its present population. A « rational depopulation » of the island should be initiated.